FUNCTIONAL-SEMANTIC ANALYSIS OF BORROWED AND AMBIVALENT HYDRAULIC ENGINEERING TERMS (EN-UZ-RU COMPARATIVE STUDY) - Babakulova Luiza Ravshanovna (International Journal of Literature and Language Studies, 2026)
This article presents a comparative functional-semantic analysis of borrowed and ambivalent hydraulic engineering terms in English, Uzbek, and Russian. The study examines three types of ambivalence — polysemy, homonymy, and synonymy — empirically illustrated through ten key terms. The findings reveal that ambivalent terms pose the highest risk of interference in translation, and their accurate interpretation requires contextual analysis and domain expertise. Patterns of phonetic adaptation and semantic shift in borrowed terms are identified, and their integration into national terminological systems is described. Drawing on the frameworks of Vinay and Darbelnet (1958), Nida (1964), and the terminological theory of Wüster (1979), linguistic strategies for minimizing interference are proposed. The results provide a foundation for standardizing hydraulic engineering terminology and compiling trilingual terminological dictionaries.